Synthesis, Identification, and anti-cancer Evaluation of Some heterocyclic Chitosan-Thiosemicarbazones compounds and their nickle (II) complexes - Mohsin Omar Mohammed; Hameed Madlool Mohammed Alkubaisi; Nadia Qader Haj (Results in Chemistry)
Chitosan (CS) a chemical substance taken from the shells of sea creatures that has various uses in industry, farming, and medicine, for example in medical dressings. Its derivatives significantly inhibit two types of cancer cells: Madin Darby Canine Kidney MDCK and MCF-7. These derivatives include thiosemicarbazones, heterocyclic moieties, and their metal (II) complexes. In this study, CS from crab shells is mixed with thiosemicarbazide (TSC). Then, imidazole-2-carboxaldehyde, oxazole-2-carboxaldehyde, and thiazole-2-carboxaldehyde reacted to make three different compounds from CS-TSC: [2a], [2b], and [2c]. The chemicals were mixed with nickel chloride to create nickel (II) chitosan 2-acetyl heterocyclic-2-thiosemicarbazone complexes. SEM and X-ray tests were performed on the powder, which showed that the nickel (II) chitosan thiosemicarbazone complexes had square and flat shapes. The synthesized compounds were tested to check their effectiveness in preventing MDCK and MCF-7. The study found that chitosan derivatives significantly inhibited MDCK and MCF-7.